2017
DOI: 10.2166/wp.2017.111
|View full text |Cite
|
Sign up to set email alerts
|

Spatial inequality in water access and water use in South Africa

Abstract: The importance of measuring inequalities in sustainable development is reflected in the requirement to disaggregate national data for the Sustainable Development Goals (SDGs). In this paper, piped water access, water use and water stress are mapped and reported at national, provincial, district, municipal, town and ward levels, and urban and rural areas. The results show that although 45% of the population has water access in their dwelling this ranges from 0.07% to 100% at ward level, with a high level of ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 6 publications
0
39
0
Order By: Relevance
“…), and within populations (e.g., Wilk and Jonsson ; Cole et al. ) is rarely rigorously quantified and carefully considered in planning applications. Exceptions exist (such as the attention given to the upstream–downstream distribution of benefits and costs in recent studies of the Great Lakes, International Joint Commission ), but have not yet appreciably impacted standard practice.…”
Section: Next Steps For Climate Change Risk Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…), and within populations (e.g., Wilk and Jonsson ; Cole et al. ) is rarely rigorously quantified and carefully considered in planning applications. Exceptions exist (such as the attention given to the upstream–downstream distribution of benefits and costs in recent studies of the Great Lakes, International Joint Commission ), but have not yet appreciably impacted standard practice.…”
Section: Next Steps For Climate Change Risk Managementmentioning
confidence: 99%
“…The remaining two components were acknowledged as important accounts for displaying additional information but would not be the principal factors in final decision-making" (Eisel et al 1982). Therefore, though it is fundamental to the values of most institutions undertaking water-resource system planning and management, equitable distribution of water, both temporally (e.g., Jeuland and Whittington 2014;Rockstr€ om et al 2014), and within populations (e.g., Wilk and Jonsson 2013;Cole et al 2018) is rarely rigorously quantified and carefully considered in planning applications. Exceptions exist (such as the attention given to the upstream-downstream distribution of benefits and costs in recent studies of the Great Lakes, International Joint Commission 2012), but have not yet appreciably impacted standard practice.…”
Section: Socio-economic and Ecological Tradeoffsmentioning
confidence: 99%
“…Luh and Bartram (2016) [ 6 ] recently analyzed progress on drinking water and sanitation in 73 countries and found that improvements in these services do not appear to be correlated with socioeconomic characteristics, but are more likely the result of policies and governance. Furthermore, cities all over the world are facing growing concerns of water stress in the face of population growth, rapid urbanization, and climate change [ 7 ]. Water demand is growing even as freshwater supplies are declining rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Although interventions designed to improve household water security are assumed to benefit residents equally, differential and unequal outcomes in areas where access to services has improved have been noted in a number of cases. This may result from a range of social, economic or institutional barriers (Cole et al, 2017;Nicol et al, 2018), such as where poor households remain locked into poor quality and inconvenient services (Carrard et al, 2019). Van Houweling et al (2017 report that in rural Mozambique the provision of handpumps reinforced existing differences in political affiliation in communities, reinforcing social divides.…”
Section: Inequalities In Household Water Securitymentioning
confidence: 99%